Experiences and Perceptions of Medical Discrimination Among a Multiethnic Sample of Breast Cancer Patients in the Greater San Francisco Bay Area, California - Quach, Thu (American Public Health Association, 2012)
Objectives. We conducted qualitative interviews with breast cancer survivors to identify themes related to institutional, personally mediated, and internalized discrimination in the medical setting. Methods. We conducted 7 focus groups and 23 one-on-one interviews with a multiethnic sample of breast cancer survivors randomly selected from a population-based registry covering the Greater San Francisco Bay Area, California. Results. Participants reported experiencing different forms of medical discrimination related to class, race, and language. Among African Americans, participants reported experiencing internalized discrimination and personal or group discrimination discrepancy—perceiving discrimination against them as a racial/ethnic group, yet not perceiving or discussing personal experiences of discrimination. Among Asian immigrants, participants reported experiencing institutional and personally mediated overt types of discrimination, including lack of access to quality and readily available translation services. Our results also indicated well-established coping mechanisms in response to discrimination experiences in both groups. Conclusions. Participants reported experiencing medical discrimination at all 3 levels, which may have deleterious health effects through the biopsychosocial stress pathway and through active coping mechanisms that could lead to delayed- or underutilization of the health care system to avoid discrimination.